Defect-induced ferromagnetism in SiC - Wang, Yutian (Saechsische Landesbibliothek- Staats- und Universitaetsbibliothek Dresden, 2015)
Defect-induced ferromagnetism is attracting intensive research interest. It not only challenges the traditional opinions about ferromagnetism, but also has some potential applications in spin-electronics. SiC is a new candidate for the investigation of defect-induced ferromagnetism after graphitic materials and oxides due to its high material purity and crystalline quality.